Early Warning, Early Action : The Use of Predictive Tools in Drought Response through Ethiopia's Productive Safety Net Programme - Drechsler, Mareile; Soer, Wolter (World Bank, Washington, DC, 2016)
This paper investigates the use of early warning tools as part of Ethiopia's Disaster Risk Management framework. Analyzing, in particular, the Livelihoods, Early Assessment and Protection tool, Livelihood Integrated Assessment and Hotspots Assessments, the paper delineates the scope and objectives of existing early warning tools, their commonalities and limitations. From a disaster risk financing and insurance perspective, the paper investigates possible enhancements in the existing early warning framework and its use that could facilitate greater timeliness of drought response. The paper argues that based on the existing early warning instruments and continued improvements to the early warning systems, it is possible to enable early action during the onset of a drought.